'Wings to fly': a case study of supporting Indigenous student success through a whole-of-university approach. Issue 1 (14th August 2021) - Uink, Bep; Hill, Braden; Day, Andrew; Martin, Gregory
Abstract: Although there have been repeated calls for empirical evaluations focused on if and how the activities of Indigenous Education Units contribute to Indigenous student success at university, data demonstrating the outcomes of these activities remain scarce. As a first step in addressing this gap, a case study of the Kulbardi Aboriginal Centre is presented which documents the development and implementation of its student success strategy. Informed by research that identifies a range of different barriers and enablers of Indigenous student success, the strategy was built around a 'whole-of-university' approach which focuses on influencing across multiple levels of the university (governance and management, teaching and pedagogy and direct student support). The success of the strategy is described in relation to changes in Indigenous student retention and pass rates. The case study offers insight into the activities of an Indigenous Education Unit, which can inform future models of practice in this area and raise awareness of the need for more comprehensive and nuanced evaluation of Indigenous higher education initiatives.